2016
DOI: 10.1038/srep30585
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of non-uniformity effect of the radial electric field on the edge transport barrier formation in JT-60U H-mode plasmas

Abstract: The turbulent structure formation, where strongly-inhomogeneous turbulence and global electromagnetic fields are self-organized, is a fundamental mechanism that governs the evolution of high-temperature plasmas in the universe and laboratory (e.g., the generation of edge transport barrier (ETB) of the H-mode in the toroidal plasmas). The roles of inhomogeneities of radial electric field (Er) are known inevitable. In this mechanism, whether the first derivative of Er (shear) or the second derivative of Er (curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…The transition from L-to H-mode plasmas is characterized by the development of an edge transport barrier, the suppression of turbulence, the formation of a negative radial electric field well in the edge and the reduction of emission [166,167]. During the L-H transition, the turbulence is decorrelated by × shear flows and by inhomogeneities in radial electric field [168]. The understanding of H-mode regimes has led to a more complete understanding of turbulent transport in high temperature plasmas for nuclear fusion.…”
Section: Iii2 Role Of Isotope Mass and Evidence Of Fluctuating Zonal Flows During The L-h Transition In The Tj-ii Stellaratormentioning
confidence: 99%
“…The transition from L-to H-mode plasmas is characterized by the development of an edge transport barrier, the suppression of turbulence, the formation of a negative radial electric field well in the edge and the reduction of emission [166,167]. During the L-H transition, the turbulence is decorrelated by × shear flows and by inhomogeneities in radial electric field [168]. The understanding of H-mode regimes has led to a more complete understanding of turbulent transport in high temperature plasmas for nuclear fusion.…”
Section: Iii2 Role Of Isotope Mass and Evidence Of Fluctuating Zonal Flows During The L-h Transition In The Tj-ii Stellaratormentioning
confidence: 99%
“…In the present case, is considered to hold 7 so that the toroidal velocity correction term for Z 2 is neglected. Recent investigation in JT-60U 8 showed an important role of not only Z 1 but also of Z 2 by referring to temperature gradient profile as an indicator of confinement intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown essential roles of an edge-localized poloidal E × B flow structure on confinement improvement 4 7 . However, definitive conclusion regarding what aspect of the E × B flow suppresses the turbulent transport is still under debate 8 . In order to obtain an understanding based on first principles, interplay between the flow structure and the turbulence must be diagnosed with high spatiotemporal resolutions, which remains challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The product of radial electric field and the 2nd derivative of the radial electric field -E r E 0 r $ as well as E 0 r was predicted to suppress the turbulence and reduce the transport. The impact of -E r E 0 r and E 0 r on the transport reduction was experimentally tested in JFT-2 M H-mode plasma [56].…”
Section: E R Bifurcation In Turbulent Transport (L-mode and H-mode)mentioning
confidence: 99%